Dexmedetomidine versus clonidine as an adjuvant to local anaesthetic in brachial plexus blocks: a meta-analysis of randomised controlled trials - Vijeta Bajpai; Tejas K. Patel; Priyanka Dwivedi; Amrita Bajpai; Astha Gupta; Pradeepika Gangwar; Yashpal Singh; Richa Agarwal; Surekha Kishore (Brazilian Journal of Anesthesiology, 2023)
Objective: This meta-analysis aimed to compare the efficacy and safety of dexmedetomidine and clonidine as an adjuvant to local anesthetics in BPBs. Methods: Two investigators independently searched databases to identify all RCTs comparing the efficacy and/or safety of dexmedetomidine and clonidine as an adjuvant to local anesthetics in BPBs. All outcomes were pooled using the inverse variance method with a random-effect model. An I2 test was used to assess heterogeneity. The source of heterogeneity was explored through meta-regression. The quality of the evidence was assessed using the GRADE approach. Results: Out of 123 full texts assessed, 24 studies (1448 patients) were included in the analysis. As compared to clonidine, dexmedetomidine groups showed significantly longer sensory block duration (MD = 173.31; 95% CI 138.02‒208.59; I2 = 99%; GRADE approach evidence: high); motor block duration (MD = 158.35; 95% CI 131.55‒185.16; I2 = 98%; GRADE approach evidence: high), duration of analgesia (MD = 203.92; 95% CI 169.25‒238.58; I2 = 99%; GRADE approach evidence- high), and provided higher grade quality of block (RR = 1.97; 95% CI 1.60‒2.41; I2 = 0%; GRADE approach evidence: moderate). The block positioning technique (regression coefficient: 51.45, p = 0.005) was observed as a significant predictor of the heterogeneity in the case of sensory block duration. No significant difference was observed for the risk of hypotension (RR = 2.59; 95% CI 0.63‒10.66; I2 = %). Conclusion: Moderate to high-quality evidence suggests dexmedetomidine is a more efficacious adjuvant to local anesthetic in BPBs than clonidine.